2019
DOI: 10.1007/s00330-018-5965-2
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of cardiac CT in the diagnosis of perivalvular complications in patients with infective endocarditis

Abstract: Objectives The aim of the study was to compare the usefulness of cardiac CT to transthoracic (TTE) and transesophageal (TEE) echocardiography in the diagnosis of infective endocarditis (IE) and perivalvular complications using surgical inspection as the gold standard. Material and methods Fifty-three consecutive patients (42 men, mean age 58.3 ± 12.5) with IE requiring surgical procedures were enrolled in the study. All patients underwent preoperative TTE, TEE, and CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 24 publications
3
68
2
3
Order By: Relevance
“…This tool shows good anatomical correlation, especially when diagnosing a perivalvular abscess of the aortomitral intervalvular fibrous body and other structures surrounding the aortic root, thus overcoming the limitations of TOE ( 75 77 ). Recent data support cardiac CT as an adjuvant exploration technique when a better depiction of valvular complications is needed or when echocardiography proves to be insufficient in both native ( 77 ) and prosthetic valve endocarditis ( 78 80 ). Furthermore, cardiac CT is frequently used to preoperatively assess the presence of coronary artery disease in aortic endocarditis where performing a coronary angiography carries a prohibitive high risk of the dislodgment of vegetations ( 74 ).…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…This tool shows good anatomical correlation, especially when diagnosing a perivalvular abscess of the aortomitral intervalvular fibrous body and other structures surrounding the aortic root, thus overcoming the limitations of TOE ( 75 77 ). Recent data support cardiac CT as an adjuvant exploration technique when a better depiction of valvular complications is needed or when echocardiography proves to be insufficient in both native ( 77 ) and prosthetic valve endocarditis ( 78 80 ). Furthermore, cardiac CT is frequently used to preoperatively assess the presence of coronary artery disease in aortic endocarditis where performing a coronary angiography carries a prohibitive high risk of the dislodgment of vegetations ( 74 ).…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…PET-CT increased the sensitivity and specificity of the modified Duke criteria from 70 to 95%, reducing the number of patients with "possible IE "from 56 to 32% [22,23]. A combination of TTE, TEE and CT can increase the sensitivity for the detection of valvular and perivalvular complications in IE [11]. Therefore, early detection of perivalvular lesions by using CT imaging should be considered in suspected IE as implemented in the recent ESC guidelines for the management of IE [9].…”
Section: Impaired Timely Diagnosis Of Pvementioning
confidence: 99%
“…Perivalvular infection is of a greater concern in PVE than NVE and occurs in 56-100% of PVE patients [1,4,10]. Previous studies suggested, that perivalvular infection worsens the prognosis, the perioperative mortality and the risk for reinfection or relapse of endocarditis [11,12]. The extension of the infection beyond the valve annulus leads to technically more demanding operations, requiring radical debridement and reconstruction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies show that central catheters are a risk factor for bacteremia and endocarditis [6,7,10]; nevertheless, Farrington et al did not find an increase of endocarditis in patients with central catheters in comparison with patients with arteriovenous fistulas [22].…”
Section: Indwelling Cathetersmentioning
confidence: 99%
“…The combination of echocardiography and CCT to diagnose abscess/pseudoaneurysm reaches 100% sensitivity. In pulmonary/right-sided endocarditis, CT may reveal concomitant pulmonary disease, including abscesses and infarcts [5,10].…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%